Psychological aspects of glycemic control in young patients with type 1 diabetes - Oleg Gennad'evich Motovilin; Yulia Andreevna Shishkova; Sergey Ivanovich Divisenko; Ekaterina Andreevna Andrianova; Elena Viktorovna Surkova; Ivan Ivanovich Dedov (Сахарный диабет)
Aim. To elucidate the relationship between glycemic control (assessed by the level of HbA1c) and psychological status of the patients. Materials and methods. The study included 115 patients with type 1 diabetes aged 13-27 years. The following tests were used to assess the psychological statusof the patients status (emotional state, social relations, attitude toward disease): State-trait-anxiety Inventory (Spielberger C.D., Hanin Y.L), Center for EpidemiologicStudies Depression Scale (CES-D), Social ajustment scale by A.K. Osnizkiy based on Q-Sort Adjustment Scale developed by R. Dymond andC.R. Rogers (1954), Lusher colour test , Colour attitudes test, A.M. Etkind original technique, method for the assessment of attitude toward disease developedin V.M. Bekhterev Research Psychoneurologic Institute, Sankt-Peterburg. The patients were allocated to 3 groups differing in terms of 33.3% percentile ofHbA1c levels. Results. Patients with good glycemic control (mean HbA1c level 7.4%) show the lowest level of social adaptation and emotional well-being. The reason for thisphenomenon is the excessive focus of patient on the disease and narrow scope of interests, which suggest psychological dependence on diabetes. Patients withpoor glycemic control (mean HbA1c level 13.1%) also experience emotional discomfort due to increased anxiety. Despite the fact they exhibit a higher degreeof social adaptation than the patients of the above group, the main concern is the low level of communicative autonomy and the feeling of being unable to copewith the disease. Such personal characteristics also create a psychological dependence on diabetes, although of a different type than in the first group of patients.Patients with average glycemic control (mean HbA1c level 9.5%) in the sample have the most favorable psychological state in comparison with the other twogroups. Their emotional state and social adaptation are significantly better than in the other two groups. These patients tend to psychological autonomy and independenceand maintain multifaceted life motivation in terms of diabetes. They perceive the disease as a given, some life condition that allows to maintaina positive psychological state, high daily activity, not to feel overwhelmed with diabetes and at the same time pay attention to diabetes self-management evennot quite sufficient.Conclusions. Glycemic control and psychological status in young adults does not coincide with each other, although there is a close relationship among them.Attitude toward the disease is the most important mediator of this relationship. Professional psychological help and educational interventions designed to developskills of the practical management of diabetes may contribute to improvement of metabolic control, psychological well-being and social adjustment of patients.